Neoliberal citizien? Pedagogical practices underlying the school citizen integral techincal model (ECIT) of the state network of Paraíba (Revista Internacional de Formação de Professores, 2023)
Considering the protagonism given to the School Citizen Integral Technical model (ECIT) in the context of the formulation of state public policies in Paraíba and the possibility of integration between citizenship education and preparation for the job market, this study analyzes pedagogical practices underlying documents of the said model. The theoretical framework is based on Foucauldian discursive studies. The corpus comprises three booklets published on the ECITs website. The analyses reveal the defense of a quick insertion of the ECIT format graduate into the job market, thus assuming a fragmented education, and the improvement of socio-emotional competencies in close accordance with the dictates of neoliberal rationality.